PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI TB. MITRA AGUNG PANGKALPINANG - Dherwahni Purba, Lisbet; Zamhari; Oktalina, Gayatria (Jurnal Progresif Manajemen Bisnis, 2019)
This study aims to find out the effects of the marketing mix consisting of product, price, promotion, place, people/human resources, physical evidence, and process, both simultaneously and partially, on the consumers’ decisions to buy at the TB.MITRA AGUNG in Pangkalpinang This was a causal associative study. The research population comprised consumers of TB.MITRA AGUNG in Pangkalpinang with an average total of 100 consumers per day. The sample was selected by means of the incidental sampling technique and it consisted of 98 consumers. The data were collected by a questionnaire. The data analysis method was multiple regression analysis. The results of the data analysis show that: (1) Product have positive and significant effects on the consumers’ decisions to buy with tobserved = 6,146 and a significance of 0.001; (2) Price have positive and significant effects on the consumers’ decisions to buy with tobserved = 3,945 and a significance of 0.001; (3) Promotion have positive and significant effects on the consumers’ decisions to buy with tobserved = 5.516 and a significance of 0.001; (4) Place have positive and significant effects on the consumers’ decisions to buy with tobserved = -1,680 and a significance of 0.096; (5) People/human resources have positive and significant effects on the consumers’ decisions to buy with tobserved = 3,181 and a significance of 0.002; (6) Physical evidence have positive and significant effects on the consumers’ decisions to buy with tobserved =-3,274 and a significance of 0.002; (7) process have positive and significant effects on the consumers’ decisions to buy with tobserved = 3,364 and a significance of 0.001;The coefficient of determination (R2) of 0.799 indicates that 90% of the consumers’ decisions to buy at the minimarket of KOPMA of YSU are affected by the variables of product, price, promotion, place, people/human resources, physical evidence, and process, while the remaining 10%.